15. PROGNOSING VALIDITY OF BIOLOGICAL CHARACTERISTICS OF COVID-19 PATIENTS AT THU DUC CITY HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: To determine the change of biological indicators in patients with COVID-19 according to the hospital stay and the mortality prognostic value. Methods: Retrospective study, monitoring medical records at Thu Duc City Hospital, Ho Chi Minh City from June 2021 to December 2021 on 269 inpatient COVID-19 patients. Record the indicators of blood cell analysis, liver and kidney function and blood coagulation of the patient in days 1, 3, 5 and the last day. Results: A decrease in platelet count and an increase in white blood cell count on the last day of follow-up, there was a difference between the mortality and survival groups. An increase in AST and ALT from 28 to nearly 60 U/L on the last day indicated liver failure, and Creatinine in the mortality group increased to 1.77 mg/dl indicating renal failure. Logistic regression analysis recorded the prognostic factors of death in patients with COVID-19 including: increase in D-Dimer, increase in neutrophils, decrease in lymphocytes and decrease in hemoglobin (p 1,126 ng/mL is the optimal cut-off value with accuracy: 66%, sensitivity: 90.57%, specificity: 60.19% and AUC=0.809; neutrophil count >6,715 x109/L has accuracy: 70.26%, sensitivity: 52.83%, specificity: 82.87% and AUC=0.726. Lymphocytes and hemoglobin both have low AUCs. Conclusion: Biological indicators have daily changes and good prognosis of mortality risk in patients.
Keywords: Patient, COVID-19, blood cell analysis, Hospital.